2020
DOI: 10.1182/bloodadvances.2020002335
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of preprocedural direct oral anticoagulant levels in patients having an elective surgery or procedure

Abstract: The Perioperative Anticoagulation Use for Surgery Evaluation (PAUSE) study prospectively evaluated a prespecified periprocedural-interruption strategy of direct oral anticoagulants (DOACs) among patients with atrial fibrillation. Logistic regression analyses were performed to identify clinical parameters associated with residual DOAC levels ≥30 ng/mL or ≥50 ng/mL. Patients undergoing low-bleed-risk procedures were more likely to have residual levels of ≥30 ng/mL and ≥50 ng/mL. For low-risk procedures, age ≥75 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 29 publications
5
40
0
2
Order By: Relevance
“…[17][18][19] Some have also suggested DOAC measurements in patients the day prior to undergoing interventions with high bleeding risk (e.g., complex endoscopy, spinal or epidural anesthesia, thoracic surgery, abdominal surgery, major orthopaedic surgery or neurosurgery), 5,[20][21][22][23] although it should be noted that this approach of measuring DOACs is currently not supported by clinical evidence and the relevance of the current threshold is questioned. 24 Specifically, although the "Perioperative Anticoagulant Use for Surgery Evaluation" (PAUSE) study reported acceptable bleeding rates with their clinically defined anticoagulant interruption strategies and defined thresholds, that is, analyses were done for residual DOAC levels 30 ng/mL and 50 ng/mL, 25,26 it is not known what DOAC level would be considered "safe" to undergo a surgical procedure or intervention and with the vast majority of patients, a wait time period appears to be safe. 25,26 With limited data on patients with a body mass index (BMI) >40 kg/m 2 , DOAC pharmacokinetic and/or pharmacodynamic measurements in this population may be considered.…”
Section: Patient Selection For Doac Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19] Some have also suggested DOAC measurements in patients the day prior to undergoing interventions with high bleeding risk (e.g., complex endoscopy, spinal or epidural anesthesia, thoracic surgery, abdominal surgery, major orthopaedic surgery or neurosurgery), 5,[20][21][22][23] although it should be noted that this approach of measuring DOACs is currently not supported by clinical evidence and the relevance of the current threshold is questioned. 24 Specifically, although the "Perioperative Anticoagulant Use for Surgery Evaluation" (PAUSE) study reported acceptable bleeding rates with their clinically defined anticoagulant interruption strategies and defined thresholds, that is, analyses were done for residual DOAC levels 30 ng/mL and 50 ng/mL, 25,26 it is not known what DOAC level would be considered "safe" to undergo a surgical procedure or intervention and with the vast majority of patients, a wait time period appears to be safe. 25,26 With limited data on patients with a body mass index (BMI) >40 kg/m 2 , DOAC pharmacokinetic and/or pharmacodynamic measurements in this population may be considered.…”
Section: Patient Selection For Doac Testingmentioning
confidence: 99%
“…24 Specifically, although the "Perioperative Anticoagulant Use for Surgery Evaluation" (PAUSE) study reported acceptable bleeding rates with their clinically defined anticoagulant interruption strategies and defined thresholds, that is, analyses were done for residual DOAC levels 30 ng/mL and 50 ng/mL, 25,26 it is not known what DOAC level would be considered "safe" to undergo a surgical procedure or intervention and with the vast majority of patients, a wait time period appears to be safe. 25,26 With limited data on patients with a body mass index (BMI) >40 kg/m 2 , DOAC pharmacokinetic and/or pharmacodynamic measurements in this population may be considered. 27,28 In addition, many elderly patients with non-valvular atrial fibrillation may acutely develop decompensated heart insufficiency with increase of liver enzymes, decreased intestinal blood flow and develop an unpredictable pharmacokinetic profile which may lead to an increased bleeding risk.…”
Section: Patient Selection For Doac Testingmentioning
confidence: 99%
“…The PAUSE study subanalysis from Shaw [ 68 ] in 2020 was performed to identify clinical parameters associated with residual DOAC levels of more than 30 ng/mL. Older age, female sex, low weight, renal dysfunction and shorter interruption were associated with risk of elevated preprocedural DOAC levels and the authors concluded that further study is required to determine whether adjustments to perioperative interruption based on these clinical parameters could result in a lower risk of residual DOAC levels.…”
Section: Optimizing Coagulation and Antithrombotic Treatmentmentioning
confidence: 99%
“…For vitamin K antagonists (VKA), the time will depend on the specific agent used: the last dose of acenocoumarol should be taken 3 to 4 days before surgery, the last dose of warfarin 6 days before surgery and phenprocoumon should be interrupted up to 10 days prior to surgery [50,56]. The PAUSE study subanalysis from Shaw [68] in 2020 was performed to identify clinical parameters associated with residual DOAC levels of more than 30 ng/mL. Older age, female sex, low weight, renal dysfunction and shorter interruption were associated with risk of elevated preprocedural DOAC levels and the authors concluded that further study is required to determine whether adjustments to perioperative interruption based on these clinical parameters could result in a lower risk of residual DOAC levels.…”
Section: Discontinuation Of Anticoagulantsmentioning
confidence: 99%
“…59 Using this feature should be considered, specially for patients who will undergo surgery and those affected by a thrombotic event in the last 30 days, for which anticoagulation should be stopped. 60,61 Removable filters should be used in individuals who have temporary restrictions on anticoagulants, and should remain for approximately 2 weeks. 62 Continuous use of these filters therapeutically is not indicated for patients not selected with DVT and candidates for the use of anticoagulants.…”
Section: Invasive Mechanical Measures and Insertion Of Inferior Vena Cava Filtermentioning
confidence: 99%